Pelatihan Kewirausahaan Bagi Ibu-Ibu Pada Komunitas Ikatan Keluarga XIII Koto Kampar Sadayoung - Rahmawati, Rahmawati; Winario, Mohd (Journal of Community Sustainability, 2025)
The urgency of entrepreneurship training for women in the Ikatan Keluarga XIII Koto Kampar Sadayoung community arises from the need to enhance the role of women in family economics and local community empowerment. This training aims to improve the entrepreneurial skills of women so that they can effectively manage independent businesses and achieve economic self-reliance. The training method used is a participatory approach, combining material presentations, group discussions, and hands-on practice to sharpen participants' technical and managerial abilities. The results of the training show an increase in entrepreneurial knowledge, product creativity development, and improved self-confidence in running a business. Participants were able to apply effective marketing and financial management techniques, which led to an increase in family income. Based on these results, it is recommended that the training be conducted continuously and its scope expanded to reach more women in the surrounding communities. Furthermore, support from the government and related institutions in the form of capital facilitation and business mentoring is crucial to ensure the success and sustainability of the women's entrepreneurial initiatives.